PERLINDUNGAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA MELALUI DIVERSI BERDASARKAN SISTEM PERADILAN PIDANA ANAK - Suryani Yusi; Erniwati Erniwati (Fakultas Hukum Universitas IBA Palembang, 2023)
ABSTRACT Children as perpetrators of these crimes must be responsible for their actions. This must be done so that it can teach the child a lesson, so that in the future the child does not repeat the same mistake. Giving punishment to children must pay attention to aspects of child development and the best interests of children. Children who commit crimes must still be protected and their rights considered so that they do not interfere with or even damage the child's growth period. The problems in this paper are what are the factors that cause children to commit crimes and how is the legal protection for children who are perpetrators of crimes in the Juvenile Criminal Justice System. regulates the protection of children in conflict with the law through diversion in Chapter II, in Articles 6, 7, 8, 9, 10, 11, 12, 13, 14